Aliansi Negara Komunis dan Fundamentalis Agama dalam Melindungi Posisi Nicolas Maduro dari Tekanan Politik Internasional Negara Barat - Nuswantoro, Bagus Subekti (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
This paper seeks to provide a view that international relations after the Cold War remains dominated by the interests of superpowers such as the United States, China and Russia. This can be seen from the behavior of these countries in influencing Venezuela. On the other hand, Turkey as a country with an Islamic Fundamentalist character under Erdogan's leadership was involved in the struggle for influence in Venezuela. What's interesting is that in this condition Turkey was in the ranks of China and Russia to support the Nicolas Maduro Government. The aim of this study is to look at the efforts of the Communist ideology (Russian) and Islamic Fundamentalism (Turkey) state in defending Nicolas Maduro's position as president of Venezuela from Western pressure.